Effect of preparation conditions on optical properties of CdTe quantum dot dispersed in water - Hung, Nguyen Van; Tuan, Duong Anh; Thien, Trinh Duc; Phu, Nguyen Dang; Do, Danh Bich; Vinh, Pham Van (VNU Journal of Science: Mathematics - Physics; Vol 28 No 1, 2012)
Abstract. CdTe quantum dots dispersed in water were prepared successfully by the microwave irradiation method. The influence of the pH value of the solution precursor, irradiation time and microwave power on the structure, size and optical properties of CdTe quantum dots was investigated. The fluorescence of CdTe quantum dots studies were illustrated that the samples which were synthesized at pH value of 7 exhibited the best fluorescence. The absorption, fluorescence spectra and TEM images showed that the microwave power and the irradiation time influenced significantly on the size of CdTe quantum dot as well as their optical properties. The fluorescence spectra were red-shift with the increase of the irradiation time and microwave power. Keywords: CdTe, Quantum dots, optical properties.